Do patients with tuberous sclerosis complex have an increased risk for malignancies?. Issue 6 (7th April 2016) - Peron, Angela; Vignoli, Aglaia; La Briola, Francesca; Volpi, Angela; Montanari, Emanuele; Morenghi, Emanuela; Ghelma, Filippo; Bulfamante, Gaetano; Cefalo, Graziella; Canevini, Maria Paola
Abstract : Tuberous Sclerosis Complex (TSC) is generally characterized by the presence of benign tumors, but some patients with malignancies have been reported in the literature. We examined a large Italian TSC population (240 individuals followed from 2001 to 2015, aged 3 months–74 years), assessing the frequency of malignancies to determine whether there is an increased risk for cancer in this disorder, and looking for possible features associated with the development of neoplasia. Fifteen patients had malignancies (6.25%); median age at diagnosis was 37.5 years (range of 1.6–58). Five of seven renal tumors were renal cell carcinomas. Eight patients had a non‐renal malignancy (3.3%), but we did not find a more prevalent type of cancer. No patient developed more than one malignancy. The prevalence of all malignant tumors was compatible with the prevalence in the general population (5.6%, 95%CI 2.99−9.31%, vs. 4.4% in Italy). Median age at cancer diagnosis was lower (37.5 years, 95%CI 28.6−44.7, vs. 66.0 years). Two patients (13.3%) died of their cancer, while outcome was favorable in the remaining individuals. Malignant tumors were more frequently diagnosed in patients with mutations in TSC1 when compared to TSC2 and patients with no mutation identified ( P = 0.032). Our study demonstrated that TSC patients do not seem to have an increased risk for malignancies besides renal cell carcinoma. However, when cancer develops, age at diagnosis is lower than in the general population, and malignant tumors are more frequently diagnosed in patients with mutations in TSC1 . Further studies are needed to confirm these data. ©2016 Wiley Periodicals, Inc.